Anomalous temperature dependence of facilitated propylene transport in silver polymer electrolyte membranes - Kim, JH; Min, BR; Won, J; Kang, YS (ELSEVIER, 2003)
Silver polymer electrolyte membranes consisting of poly(vinyl pyrrolidone) (PVP) and AgBF4 have previously exhibited remarkable separation performance with respect to propylene/propane gas mixtures. In this work, the effect of temperature on facilitated propylene transport is reported. The propylene permeance through the PVP/AgBF4 membranes decreased with increasing temperature, predominantly due to a decrease of the propylene concentration coordinated to silver ions; that is propylene solubility, as demonstrated by FT-IR spectroscopy. The propane permeance and the actual selectivity of propylene over propane decreased monotonously with increasing temperature. Unexpectedly, the propylene permeance further drops sharply when the temperature is increased higher than 70degreesC. This anomalous behavior of the propylene permeance at temperatures above 70 degreesC can be explained by the deactivation of silver ions as active olefin carriers, i.e. the reduction of silver ions to silver metals. It is concluded that the silver ions as active olefin carriers rapidly convert to silver metals at temperatures above 70 degreesC, therefore becoming much less active olefin carriers, which results in the low propylene permeance. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: DENSITY-FUNCTIONAL THEORY; COMPLEX MEMBRANES; OLEFIN TRANSPORT; PERMEATION; IONS; NANOPARTICLES; MECHANISM; PROPANE; SEPARATION; ENERGIES